Identifikasi Telur Cacing Nematoda Usus Soil Transmitted Helminth (STH) Pada Masyarakat Di Pulau Lae-Lae Kota Makassar - Anita Anita; Tuty Widyanti; Effendy Rasiyanto; Budiawan S.HI. Karim (Lontara Journal of Health Science and Technology, 2021)
ABSTRACT Communities on Lae-Lae Island, Makassar City have sanitation facilities that are still poor and very limited with quality far from health standards. This causes people who live in these islands to face various health problems, one of which is the risk of being infected with eggs of intestinal nematode worms Soil-Transmitted Helminths (STH). This study aims to identify the eggs of the intestinal nematode worm Soil Transmitted Helminthes in the feces of people on Lae-Lae Island, Makassar City. This type of research is a laboratory observation with a purposive sampling technique of 10 stool samples. Based on the results of research that has been carried out on 10 faecal samples, it was found 1 positive stool sample for Trichuris trichura worm eggs with distinctive egg-shaped characteristics such as the shape of crock worm eggs or wine barrels and at both ends there are two mucoid plugs. The egg wall is brown from the color of the bile at both ends, it is clear, while the other 9 stool samples are negative the type of worm Trichuris trichura and 9 other samples were negative.